PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA ALPHA HOTEL PEKANBARU - Sariwati Simarmata; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of recruitment and job placement tehadap employee performance at Alpha Hotel Pekanbaru. where proposed two independent variables and one dependent variable, namely recruitment and job placement as independent variables and employee performance as a dependent variable.This research method is descriptive and quantitative by using SPSS 21 program, where the sample used is employees of Alpha Hotel Pekanbaru with 78 respondents. For sampling technique using census method. Technique of collecting data through kusioner and interview.The results of analysis using the validity test, reliability test, detemination test, simple linear regression test, multiple linear regression test, t test, and f test so it can be seen that recruitment has a significant effect on employee performance, that work placements have significant effect on employee performance, recruitment and job placement have a significant effect on employee performance. Keywords: Recruitment, job placement, and employee performance.